A biomimetic mesh for treating female stress urinary incontinence. (4th January 2017) - Lai, Kuilin; Zhang, Jiazhen; Wang, Guoshuai; Luo, Xin; Liu, Man; Zhang, Xinzhi; Yuan, Yuyu; Liu, Bin; Xu, Tao
Abstract: For patients with medium to severe incontinence, sub-urethral support surgery has a high cure rate, but using synthetic meshes leads to some complications such as mesh erosion/exposure and thigh pain. Autologous or acellular extracellular matrix grafts present few complications but have a high recurrence rate. Regensling ™ is a new sling product made of a synthetic material with a biomimetic structure, aiming to provide long-term mechanical support with a lower complication rate. To assess the safety and effectiveness of Regensling ™, both in vitro and in vivo experiments were performed. The mesh was implanted in the subcutaneous, intramuscular and sub-urethral regions of rabbits. At 4, 12, and 26 weeks post-implantation, the animals were executed and the implants were studied for their mechanical and biocompatible properties. Compared to the control material, the Regensling ™ was covered by a thin layer of fibrous tissue with good compliance, and had a milder inflammatory response. During the period of the experiment, Regensling ™ showed stable strength with an increasing trend over time.